Cholesteryl ester transfer protein (CETP) as a drug target for cardiovascular disease - Schmidt, Amand F.; Hunt, Nicholas B.; Gordillo-Marañón, Maria; Charoen, Pimphen; Drenos, Fotios; Kivimaki, Mika; Lawlor, Deborah A.; Giambartolomei, Claudia; Papacosta, Olia; Chaturvedi, Nishi; Bis, Joshua C.; O’Donnell, Christopher J.; et al. (Nature communications, 2021)
Development of cholesteryl ester transfer protein (CETP) inhibitors for coronary heart disease (CHD) has yet to deliver licensed medicines. To distinguish compound from drug target failure, we compared evidence from clinical trials and drug target Mendelian randomization of CETP protein concentration, comparing this to Mendelian randomization of proprotein convertase subtilisin/kexin type 9 (PCSK9). We show that previous failures of CETP inhibitors are likely compound related, as illustrated by significant degrees of between-compound heterogeneity in effects on lipids, blood pressure, and clinical outcomes observed in trials. On-target CETP inhibition, assessed through Mendelian randomization, is expected to reduce the risk of CHD, heart failure, diabetes, and chronic kidney disease, while increasing the risk of age-related macular degeneration. In contrast, lower PCSK9 concentration is anticipated to decrease the risk of CHD, heart failure, atrial fibrillation, chronic kidney disease, multiple sclerosis, and stroke, while potentially increasing the risk of Alzheimer’s disease and asthma. Due to distinct effects on lipoprotein metabolite profiles, joint inhibition of CETP and PCSK9 may provide added benefit. In conclusion, we provide genetic evidence that CETP is an effective target for CHD prevention but with a potential on-target adverse effect on age-related macular degeneration. Despite being studied in clinical trials, CETP inhibitors are not yet an approved treatment for coronary heart disease. Here, by analyzing results from clinical trials and drug target mendelian randomization studies, the authors demonstrate that previous failure of CETP inhibitors are likely compound and not drug target-related.